Early readmissions after transcatheter and surgical aortic valve replacement. Issue 4 (2nd March 2017) - Vejpongsa, Pimprapa; Bhise, Viraj; Charitakis, Konstantinos; Vernon Anderson, H.; Balan, Prakash; Nguyen, Tom C.; Estrera, Anthony L.; Smalling, Richard W.; Dhoble, Abhijeet
Abstract : Objectives: We aimed to determine and compare the prevalence, and predictors of readmissions after the transcatheter aortic valve replacement (TAVR) and surgical aortic valve replacement (SAVR). Background: There are limited data on the readmission rates after TAVR in comparison with SAVR. Methods: We analyzed the data from 2013 National Readmission Database. Propensity‐matched pairs were used to analyze differences in readmission rates between TAVR and SAVR for patients aged ≥65. Results: A total of 24, 020 (TAVR‐transfemoral 3, 469, TAVR‐transapical 1, 433, SAVR 19, 118) patients were included. The readmission rates were not statistically different for all propensity‐matched TAVR and SAVR patients (17.2% vs. 20.6%, P = 0.28). However, in subgroup analysis, transapical TAVR had the highest readmission rate (22.8% vs. 16.5% vs. 16.0%, P < 0.001, respectively) and readmission leading to death (7.1% vs. 5.3% vs. 3.9%, P = 0.022, respectively) when compared with transfemoral TAVR and SAVR. In all the groups, two‐thirds of readmissions were due to noncardiac causes. Congestive heart failure (CHF) and arrhythmia were the most frequent cardiac etiologies. The independent predictors of readmission were female sex, CHF, and chronic obstructive pulmonary disease. Patients who received care in teaching hospitals had lower probability of readmission. Conclusions: One of six patients were readmitted within 30 days after the aortic valve replacement. On propensity score analysis, there were no significant differences between the early readmission rates between TAVR and SAVR groups. However, the patients undergoing transapical TAVR were at higher risk for readmission, and subsequent deaths when compared with transfemoral TAVR and SAVR. © 2017 Wiley Periodicals, Inc.